What Influences the Historical Memory of Modern Students? - N. D. Sorokina (Высшее образование в России)
Historical memory is an object of informational conflict. This is why it is so important to study this phenomenon. Using the example of a survey of students in relation to important historical events in our country, including the Great Patriotic War, it is shown that while there is no radical transformation of the role of the past in the formation of personality, in the minds of most young people, historical memory is still a good form of patriotism education. The most effective mechanisms for preserving the memory of historical events are social institutions of education and family. At the same time, there is a “fading” of such a traditional and effective mechanism for preserving the memory of the Great Patriotic War as personal meetings with war veterans, personal communication with relatives who passed the war. It can be replaced by a mechanism for preserving memory, such as memoir literature of war participants, which is not yet popular among students. However, there is a problem: personal historical memory sometimes goes against the official interpretation of historical events. It can also serve as a mirror image of the social divide in society. In addition to traditional social institutions, civil society institutions can play an important role in shaping shared historical memory. If the latter are supported by the state, it is possible to avoid a conflict between cultural memory, which is closely related to traditions, and communicative memory. If these channels operate separately, or if, say, ideology tries to suppress other channels, historical memory is devalued and distorted. If all these channels work synchronously, they provide a huge effect. Different types of memory perform an important function – education of a citizen who would be responsible to past generations and to descendants.